DETERMINATION OF COOKING END POINT AND TIME FOR STEAKS OF CATLA CATLA AND JOHNIUS GANGETICUS - KAR, S; CHOWDURY, S; DORA, K C; NATH, S; CHANDRAVANSHI, N K; SINGH, S M (Journal of the Inland Fisheries Society of India, 2021)
Heat is applied to cook the fish before consumption to enhance their flavor and taste, inactivate pathogenic microorganisms and increase shelf life. The cooking endpoint is usually characterized by sensory attributes, thus formation of attractive surface browning and crust, crispiness, development of aroma compounds and optimum inner cooking. Here deep frying 130 o C (T1), 150 o C (T2), 180 o C (T3), microwave (2450 MHz) (T4), boiling (T5) and steaming (T6) of Catla and Croaker steaks were done. Based on the sensory evaluation, a frying condition of 180 o C for 4.5 minutes for Catla and 180 o C for 2.5 minutes for Croaker were best.Key Words: Cooking-endpoint, deep-frying, Catla, Croaker, sensory evaluation.